Violence, security perception and mode choice on trips to and from a university campus - Silva, Denise Capasso da (2017)
This dissertation addresses the validation of the hypothesis there is a general sense that violence and security perception influence the use of sustainable travel modes. The research characterizes the issue of security perception among University of São Paulo (Brazil) users and identifies the way the sense of security and violence occurrences are related to the travel mode choice. An online survey on security perception and the way its participants access the campus was conducted. The target relationships were explored by Decision Tree (DT) algorithms. An initial exploratory analysis revealed occurrences of violence and reports of insecurity perception were strongly correlated on streets around the campus. The time analysis of violence distribution presented the incidents concentrated at night and during the week. The study also showed that security perception variation according to gender and travel mode choice is less sensitive to security perception than to the occurrence of violence, or type of affiliation to the university. Finally, DT algorithms explored the relation of spatially treated variables (i.e. route length to the university, density of violence occurrences and insecurity reports on the route) to mode choice. The results also showed that distance to the campus was relevant to the mode choice only in routes not strongly considered unsafe. In routes of higher insecurity perception, the share of nonmotorized modes was more expressive and the largest participation of sustainable modes was on routes with high incidence of violence. Since it is counterintuitive to assume numerous walking trips are a consequence of violence, the opposite was considered as a possible explanation to those results. The present study reinforces the need for increased surveillance in regions with high participation of non-motorized modes, for preventing users from shifting to motorized modes.